ҲАМИД АРАСЛИ — НАВОИЙШУНОС - Tojiboyeva, Ozoda (FILOLOGIYA UFQLARI JURNALI, 2022)
Cooperation between the Azerbaijani and Uzbek peoples in the fields of literature, art and culture dates back many centuries. Literary influence, the works of Nizami Ganjavi and Alisher Navoi, Navoi's work and Azerbaijani literature, which are at the centre of literary relations, are important research objects for both literary studies. Prominent scholars have done research based on comparative analysis and made significant contributions to the study of the writerʼs creative heritage. The fruitful work of the doctor of philological sciences, academician Hamid Arasli is especially noteworthy. This article describes the contribution of Azeri scientist Hamid Arasli to Navoi studies. His participation in conferences dedicated to the birth of Navoi is indicated. His articles, such as “Navoi and Azerbaijani literature”, “History of studying Navoi heritage”, published in the journals “Uzbek language and literature” and “Literary heritage” were observed. Important facts and the scientific value of H. Arasli's research is proved. The study describes Navoi's influence on Azerbaijani tazkirism and his views on determining the author of the work "Sabat abhur". Scientific cooperation of H.Arasli with Uzbek scientists has been noted as well.